Pengembangan Video Animasi Berbasis Aplikasi Inshot Pada Materi Keberagaman Budaya Di Indonesia Kelas IV Sekolah Dasar - Bella Kasari; Fandi Nugroho; Rifki Hanif Setiawan (Universitas Muhammadiyah Bangka Belitung, 2025)
This research is motivated by the lack of utilization in using creative and innovative learning media. Teachers use visual learning media, such as pictures and books. Students are less enthusiastic about participating in learning activities. This research aims to produce a product in the form of an animated video based on the inshot application that is valid, practical and effective on cultural diversity material in class IV elementary schools in Indonesia. This research uses Research and Development (R&D) with the ADDIE model, which consists of the Analyze, Design, Development, Implementation and Evaluation stages. The research subjects were 16 grade IV students at SD Negeri 43 Pangkalpinang. Interviews and questionnaires are data collection techniques. The data analysis technique used is quantitative descriptive using a Likert scale. The research results show that animated video media is based on the inshot application on Cultural Diversity in Indonesia material, with a validity percentage given by media experts of 92% (very valid), material experts 100% (very valid) and 100% (very valid). The small scale trial consisting of 5 class IV students obtained a percentage of 88.8% (very practical) while the large scale trial of 16 class IV students obtained 95.5%, (very practical). Results of the paired sample t-test t_(count ) 6,299 > t_table 2,085. Thus, H_a is accepted, meaning there are differences before and after the use of learning media.